Conditioning of simulated cesium radionuclides in NaOH-activated fly ash-based geopolymers. (20th December 2022) - Jain, Shubham; Banthia, Nemkumar; Troczynski, Tom
Abstract: The growing nuclear safety concerns call for better solutions than traditional Portland cement-based materials to retain radionuclides especially Cesium (Cs). This work explored engineering process development and characterization of low-cost sustainable NaOH-activated fly ash-based geopolymers (FA-GP) as a conditioning matrix for non-radioactive equivalent of Cs (133Cs + ). The effects of processing parameters on the FA-GP microstructure, porosity, in-situ zeolite crystallization, and Cs immobilization performance (quantified as the Leachability Index LX ) were investigated and compared with literature data. The immobilization of non-radioactive equivalent of Cs (133Cs + ) in NaOH-activated FA-GP was investigated using factorial design of experiments. The Cs leachability index ( LX ) was evaluated according to ANSI/ANS-16.1. FA-GP were characterized using SEM, XRD, and N2 adsorption-desorption isotherms. The results revealed that the main factors influencing Cs immobilization were the curing temperature and the interaction between Cs dosage and curing temperature. LX  ≥12 and effective diffusion coefficient D e  ≤10 −12  cm 2 /s was obtained for FA-GP cured at 90 °C. The effective diffusivity was about 5–7 orders of magnitude lower than for the conventional Portland cement-based encapsulation materials. Enhanced immobilization of Cs ( LX  = 14.6, D e  = 2.5 × 10 −15  cm 2 /s), not reported hitherto, was further achieved by in-situ pollucite (Cs, Na)2 Al2 Si4 O12 .2H2 O crystallization within FA-GP via one-step synthesis route at 90 °C. In addition, leaching studies on powdered FA-GP demonstrated encouraging performance and reliability of FA-GP under extreme mechanical conditions. It therefore appears that FA-GP could be a promising nuclear waste immobilization material, especially for the waste containing high concentration of Cs. Graphical abstract: Image 1 Highlights: Effects of process parameters on cesium immobilization in fly ash-based geopolymers were studied Fly ash-based geopolymers exhibited exceptional immobilization performance In-situ pollucite crystallization in geopolymer was achieved at <100 °C Cesium was immobilized both chemically and physically in geopolymers